2012
DOI: 10.1177/0022146512462888
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Mental Health, Behavior Problems, and Academic Achievement

Abstract: Prior research on the association of mental health and behavior problems with academic achievement is limited because it does not consider multiple problems simultaneously, take co-occurring problems into account, and control for academic aptitude. We addressed these limitations using data from the National Longitudinal Study of Adolescent Health (N = 6,315). We estimated the associations of depression, attention problems, delinquency, and substance use with two indicators of academic achievement (high school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
178
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(206 citation statements)
references
References 67 publications
15
178
2
4
Order By: Relevance
“…Tal dado está de acordo com a literatura que indica que a falta de atenção acarreta dificuldades para estudar e se concentrar, o que, consequentemente, está associado ao pior rendimento escolar (Casali-Robalinho, Del Prette, & Del Prette, 2015;McLeod, Uemura, & Rohrman, 2012;Romano et al, 2010). Valverde et al (2012) também ressaltaram que as tarefas escolares exigem dos adolescentes esforço consciente e contínuo para manter o foco, sendo que as dificuldades de atenção encontradas no início da escolarização podem levar ao baixo rendimento escolar no futuro.…”
Section: Discussionunclassified
“…Tal dado está de acordo com a literatura que indica que a falta de atenção acarreta dificuldades para estudar e se concentrar, o que, consequentemente, está associado ao pior rendimento escolar (Casali-Robalinho, Del Prette, & Del Prette, 2015;McLeod, Uemura, & Rohrman, 2012;Romano et al, 2010). Valverde et al (2012) também ressaltaram que as tarefas escolares exigem dos adolescentes esforço consciente e contínuo para manter o foco, sendo que as dificuldades de atenção encontradas no início da escolarização podem levar ao baixo rendimento escolar no futuro.…”
Section: Discussionunclassified
“…Adolescents' performance at school and their own plans for the future are likely to be related to their future socioeconomic status, and thus may also be an indicator of their likelihood to smoke in the future (Baumrind et al, 1991). Studies by Bryant et al (2000), Park et al (2011) and Mcleod et al (2012) suggested that poor academic performance is associated directly or indirectly with increased cigarette use among adolescents. According to a recent study by Morin et al (2011), adolescents who do well in school are less likely to smoke.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, students with attention problems and one or more additional problems achieved a lower level of education compared with those who 'only' had one problem. The conclusion drawn is that behaviour problems in students are not due to low learning ability, but rather to attention problems and both school and social contexts (McLeod et al, 2012).…”
Section: Who Suffer From Wm-deficits?mentioning
confidence: 97%